2007
DOI: 10.1007/s10038-007-0118-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of a chromosome 1q21 locus in close proximity to a late cornified envelope-like proline-rich 1 (LELP1) gene with total serum IgE levels

Abstract: The chromosomal region 1q21 has been linked to atopic dermatitis in previous studies. Seven polymorphic repeats were identified in a 0.5 Mb region of chromosome 1q21 encompassing a small prolinerich protein (SPRR) gene cluster, a few S100 gene family members, loricin, and several uncharacterized genes. These repeats were genotyped by fragment length polymorphism analysis in 133 atopic case-parent trios, of which 111 probands had atopic asthma. Our trio-based analysis for association with atopy and atopic asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Some authors [35], have found an association of this chromosome 1q21 tagged single nucleotide polymorphism (SNPs) within the LELP1 gene [rs7534334] with serum IgE levels. These results pointed to the need for research on LELP1 and other genes on EDC that could be related with many inflammatory diseases of the skin like AD and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors [35], have found an association of this chromosome 1q21 tagged single nucleotide polymorphism (SNPs) within the LELP1 gene [rs7534334] with serum IgE levels. These results pointed to the need for research on LELP1 and other genes on EDC that could be related with many inflammatory diseases of the skin like AD and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors [35], refer a correlation of log10 serum IgE levels and rs7534334 in a group of asthmatic patients being the mutant genotype (TT) in patients, those with higher levels of IgE comparing with controls (TT) and comparing with wild type genotype (CC) in patients (3.49 ± 0.91 vs 2.43 ± 0.52 vs 2.92 ± 0.59) .This point to the works who showed that when skin barrier function is compromised even without skin disease there is an increased incidence of atopic disease [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gene encodes a late cornified envelopelike prolin-rich protein. Indian scientists found a significant link between rs7534334 SNP and log10 serum IgE levels in the group of patients (Sharma et al 2007). However, this was only a single study and the authors stressed the need for further research.…”
Section: Role Of the Skin Barriermentioning
confidence: 99%